2011
DOI: 10.1016/j.jmii.2011.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium subsp paratuberculosis—Incidences in milk and milk products, their isolation, enumeration, characterization, and role in human health

Abstract: Mycobacterium avium subsp paratuberculosis (MAP), excreted in the feces and milk, is reported to be not easily inactivated by pasteurization and thermal treatments as other bacteria infecting humans and animals do. The D values of all MAP strains tested were considerably higher than those published for other pathogens. Culturing techniques for this organism are labor intensive. Although an increasing amount of scientific evidence suggests that this organism can be responsible for at least some cases of Crohn's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 73 publications
0
16
0
2
Order By: Relevance
“…More significantly, several reports have suggested that M. avium subsp. paratuberculosis might survive milk pasteurization procedures (12)(13)(14).…”
mentioning
confidence: 99%
“…More significantly, several reports have suggested that M. avium subsp. paratuberculosis might survive milk pasteurization procedures (12)(13)(14).…”
mentioning
confidence: 99%
“…Frequent detection of MAP DNA in blood of humans may be due to the wide distribution of MAP in the environment and its presence in the food chain. MAP‘s recent isolation from meat products [48-50] and its presence in milk [51], makes these part of a transmission route that goes direct to human beings if these are not cooked appropriately [52]. The observation of higher frequencies of MAP in healthy controls than in patients is controversial, but it is compatible with a slow infection model of pathogenesis where healthy carriers that do not develop the disease are a larger proportion of the population than that showing clinical signs.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional etiological studies on CD and Map have been carried out under the hypothesis that “Map infection” causes CD (Behr and Kapur 2008; Gill et al 2011; Hermon-Taylor et al 2000). The effect of a “ Map antigen” that can contaminate dairy products (Eltholth et al 2009; Foods 2010; Hermon-Taylor et al 2000; Millar et al 1996; Patel and Shah 2011) and meat (Alonso-Hearn et al 2009; Gill et al 2011; Klanicova et al 2011) from Ptb-infected cattle on human health was not reflected as an etiology of CD (Economou and Pappas 2008; Glasser and Darfeuille-Michaud 2008; Lakatos 2009; Umeno et al 2011). As many previous studies have indicated, the detection of Map -specific DNA IS900 by PCR from human intestine, blood, and feces (Abubakar et al 2008; Chiodini 1989; Tuci et al 2011) or by in situ hybridization in intestines (Romero et al 2005) may be evidence of exposure to the Map antigen complex but does not always mean the presence of live Map .…”
Section: Discussionmentioning
confidence: 99%